Stable single atomic silver wires assembling into a circuitry-connectable nanoarray - Yaxin Chen (Nature Portfolio, 2021)
One-dimensional atomic metal wires can exhibit useful properties distinct from their bulk equivalents; however they typically suffer from limited stability. Here, Chen et al create atomic silver wires which are stable and exhibit a temperature dependent metal to insulator transition.